Comparative analysis on the ILO Indigenous and Tribal Peoples Convention No. 169, UN Declaration on the Rights of Indigenous Peoples (UNDRIP), and Indigenous Peoples’ Rights Act (IPRA) of the Philippines - Candelaria, Sedfrey M (Archīum Ateneo, 2012)
In 1989, the Indigenous and Tribal Peoples Convention No. 169 was adopted by the International Labour Organization (ILO). ILO Convention No. 169 is a comprehensive instrument that covers a wide range of issues concerning indigenous peoples, including land rights, access to natural resources, health, education, vocational training, conditions of employment, and contacts across borders. It is by far the only international legal instrument that is open for ratification which exclusively deals with the protection of indigenous and tribal peoples’ rights. Once ratified, there is an obligation to apply all its requirements in law and in practice. Its ratification by the Philippines is currently under consideration. The Philippines, in the meantime, has enacted Republic Act No. 8371 or the Indigenous Peoples’ Rights Act (IPRA) of 1997. It is a law that is designed to protect and promote the rights of the indigenous peoples. The IPRA is consistent with the policy and principles of ILO Convention No. 169. For its part, the United Nations General Assembly has adopted in 2007 the UN Declaration on the Rights of Indigenous Peoples (UNDRIP). The UNDRIP consolidates and affirms the mandate of governments to address all issues concerning the rights of indigenous peoples. It complements, reinforces and reaffirms the principles of ILO Convention No. 169. The ILO commissioned a “Comparative analysis on ILO Convention No. 169, the UN Declaration on the Rights of Indigenous Peoples (UNDRIP), and the Indigenous Peoples’ Rights Act (IPRA) of the Philippines”. The study is part of the continuing effort to promote ILO Convention No. 169 and to contribute to the empowerment of the indigenous peoples through technical cooperation activities. This undertaking was inspired by the sustained enthusiasm of various sectors and stakeholders to promote the ratification of ILO Convention No. 169 and the full implementation of the IPRA. These stakeholders include indigenous peoples through their councils and institutions, cause-oriented civil society organizations and concerned government agencies. To them, it is important to have a workable framework within which to understand and appreciate the relationship of the three instruments. A reading of this study invariably leads to the conclusion that indeed ILO Convention No. 169, UNDRIP, and IPRA complement each other. The analysis, although legally and technically oriented, is understandable to all types of readers. It has specifically highlighted how indigenous peoples and the nation as a whole would benefit from ratifying ILO Convention No. 169. I hope that this study would encourage more enlightened discourse and exchanges on the underlying principles and complementation that exist between ILO Convention No. 169, UNDRIP, and the IPRA among practitioners and advocates of indigenous peoples rights protection and empowerment. Lawre